Poly[[hexa-μ-aqua-diaquabis(μ(4)-dihydrogen benzene-1,2,4,5-tetracarboxylato)magnesiumdisodium] dihydrate] - Zhao, Dan (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, {[MgNa(2)(C(10)H(4)O(8))(2)(H(2)O)(8)]·2H(2)O}(n), contains one octahedrally coordinated Mg(II) atom (site symmetry 2/m), one octahedrally coordinated Na(I) atom (site symmetry 2) and one half of the dihydrogen benzene-1,2,4,5-tetracarboxylate (btec) ligand, the second half of the ligand being generated by a twofold rotation axis. The basic framework of the title compound features infinite (–Na–Na–Mg–)(n) chains along [10-1] with the metal cations bridged by the coordinating water molecules. The chains are isolated from each other by μ(4)-bridging btec ligands, which form intermolecular O—H⋯O hydrogen bonds to uncoordinated water molecules and the coordinated water molecules of a neighbouring chain. In each btec ligand, there are also intramolecular O—H⋯O hydrogen bonds.